BUDAYA TAREK PUKAT DALAM MANAJEMEN STRATEGI KEPEMIMPINAN MASYARAKAT PESISIR - Febriana, Dennik; Wihara, Dhiyan Septa; Leksono, Poniran Yudho (Universitas Nusantara PGRI Kediri, 2023)
This paper explores the Tarek Pukat Culture from Aceh to interpret local wisdom-based leadership performance practices for coastal communities in Indonesia. The informants were five fishermen on Ujong Blang Beach, Lhokseumawe, North Aceh. Alfred Schutz's phenomenological research approaches through in-depth interviews. This study shows that fishermen consider the meaning of loyalty not limited to material gain or position at work, but also presents a new view of the values of wisdom in human resource management strategies. Tarek Pukat's dance and poetry represent a strategy to maintain their enthusiasm and loyalty based on spiritual values. The unique character which is not included in conventional leadership concepts recommends increasing leadership strategies with the meaning of Tarek Pukat Culture to the community, especially coastal communities in Indonesia. Community groups can achieve sustainable performance as large as transformational leadership even though pursuing material gain is not their main goal to maintain their loyalty to community groups, especially in coastal areas.